Eksperimentasi Model Pembelajaran Problem Based Learning dalam Pembelajaran Nahwu di Kelas X SMA - Muhammad Sya'dullah Fauzi (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
This study aims to find out how the application of the problem based learning (PBL), and the learning outcomes of Nahwu students; and to know the effect of the problem based learning model on Nahwu results at Wahid Hasyim Sleman High School. This type of research is Experimental Research with comparative data. The subject of this research is class X Mipa 1 as an experimental class and class X IPS as a control class. The results of this study indicate that the average experimental class students before applying the PBL learning model is 74. While the average control class students before being given treatment is 72. The average experimental class students after applying the PBL is 85, and the average control class after being given a treatment of 74. From the results of the T test analysis obtained a significance value of 0,000. That is, the PBL is influential in improving student Nahwu learning outcomes. This shows that the class given a PBL model on average is bigger than the class applied in the conventional learning model. The difference is significant. That is, the PBL model is influential in improving the learning outcomes of Nahwu.